2020
DOI: 10.1021/jacs.0c11061
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Powered Porous Micromotors Built from a Hierarchical Micro- and Mesoporous UiO-Type Metal–Organic Framework

Abstract: Enzyme-powered porous micro-and nanomotors combine self-propelled motion with tailored functionalities like adsorption and release, making them very attractive for myriad applications. Here, we report the design, synthesis and functional testing of enzyme-powered porous micromotors built from a metal-organic framework (MOF). We began by subjecting a pre-synthesized microporous UiO-type MOF to ozonolysis, to confer it with mesopores sufficiently large to adsorb and host the enzyme catalase (size: 6-10 nm). We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 56 publications
2
69
0
Order By: Relevance
“…Crucially, these highly porous MOFs could initially only be attained with the use of very long linkers, resulting in generally unstable systems. In this context, Yang et al proposed the idea of subjecting the MOF to ozonolysis to generate mesopores wide enough for catalase immobilization [23].…”
Section: The Origins and Rising Dominance Of The Enzyme-supporting Mofmentioning
confidence: 99%
“…Crucially, these highly porous MOFs could initially only be attained with the use of very long linkers, resulting in generally unstable systems. In this context, Yang et al proposed the idea of subjecting the MOF to ozonolysis to generate mesopores wide enough for catalase immobilization [23].…”
Section: The Origins and Rising Dominance Of The Enzyme-supporting Mofmentioning
confidence: 99%
“…The retained free space was also used for the adsorption removal of Rhodamine-B during the self-propulsion. 49 Pumera et al recently reported rod-like MOF microrobots for the removal of radioactive species in water. 50 The latter were developed by selectively depositing Pt on one side of the rods pre-synthesized through membrane-based interfacial reaction (Fig.…”
Section: Supramolecular Framework: Organic-inorganic Hybrid Crystalli...mentioning
confidence: 99%
“…Thanks to the open mesochannels and designable topology, full advantages of hierarchical mesoporous Zr-based metal–organic frameworks (mesoMOFs) could be taken for constructing such a heterogeneous system. Their rigid and stable mesochannels could work as exoskeletons to immobilize and protect natural SOX. Meanwhile, the phosphorescent carboxylated metalloporphyrin of TCPP-Pt could serve as colinker to be well incorporated into the surrounding microporous walls as oxygen-sensitive signal units (Scheme ). Metallic nodes in MOFs could effectively isolate TCPP-Pt, thus avoiding the aggregation-induced quenching effect .…”
Section: Introductionmentioning
confidence: 99%